An Empirical study to Measuring Corruption and Integrity in Kenyan Police Agency: An Ethical Perspective - Mathenge, Githui Donatus (2014)
Integrity is universal to human experience; it can be considered the measure of an individual, an agency, an institution, a discipline, or an entire nation. Integrity is a yardstick for trust, competence, professionalism, and confidence. A growing body of literature on police officers regarding integrity issues focuses on their perceptions of corruption prevalence. Currently, the police sector in Kenya is undergoing reforms which includes vetting of the top officers as stipulated in the new constitution dispensation of 2010.But this exercise has not decreased corruption in the police service .Even the ongoing traffic law enforcement at various road blocks in all corners of the country seems to have widened the window of bribery and corruption in the police traffic chain. Recently, even the president admitted that the police officers serving in the statehouse thrive on corruption and bribery and promised stun action against them. Integrity seems to be very elusive and a mirage in the police sector. The current analysis sought to examine empirically and determine corruption and integrity in the Kenyan Police Agency, with an ethical inclination. Data was collected through self-administered questionnaires by the researcher. Data was analyzed through descriptive statistics, multiple regression analysis and correlation analysis. Results indicate a significant relationship between ethics and corruption in the Kenyan police force. In this regard, there is a need to inculcate ethical integrity into the whole process of police administration in Kenyan Police Agency. This paper helps police management by providing useful information on ethics and corruption in Kenyan police organization and how they can benefit from this information in reducing the opportunity for corruption among members of this critical service agency. Keywords: Ethical Policing, police integrity, professionalism, occupational culture, organizational rules,corruptio